2012
DOI: 10.1002/anie.201201288
|View full text |Cite
|
Sign up to set email alerts
|

Incarceration of (PdO)n and Pdn Clusters by Cage‐Templated Synthesis of Hollow Silica Nanoparticles

Abstract: Ein sphärischer Pd12L24‐Komplex dient als Templat bei der Synthese von hohlen Siliciumdioxidnanopartikeln, die Metallcluster mit definierter Atomzahl n in ihrem Inneren enthalten. Der eingeschlossene Pd12L24‐Komplex wird in der schützenden Siliciumdioxidhülle zunächst in einen (PdO)n‐Oxidcluster umgewandelt und anschließend zum Pdn‐Metallcluster reduziert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 31 publications
(2 reference statements)
1
19
0
Order By: Relevance
“…In both the reported r ‐space EXAFS spectra of PdO nanoparticles and our studies of reference PdO sample, a peak at 3.1 Å was clearly identified, comparable in intensity to be the first nearest neighbor Pd−O contribution; this peak at 3.1 Å represents the contribution to EXAFS from the two closest Pd atoms in a PdO nanoparticle, bridged by an oxygen atom (Pd−O−Pd). Compared to other PdO nanoparticles and the reference PdO sample (red line in Figure ), however, the r ‐space spectrum of 0.04 wt % Pd/ZSM‐5 (blue line in Figure ) does not have such a distinct peak with the similar intensity as the Pd−Pd peak in PdO at ∼3.1 Å. Therefore, there is no evidence that any species or structure in 0.04 wt % Pd/ZSM‐5 contains Pd−O−Pd species, which indicates the absence of PdO nanoclusters.…”
Section: Figuresupporting
confidence: 54%
“…In both the reported r ‐space EXAFS spectra of PdO nanoparticles and our studies of reference PdO sample, a peak at 3.1 Å was clearly identified, comparable in intensity to be the first nearest neighbor Pd−O contribution; this peak at 3.1 Å represents the contribution to EXAFS from the two closest Pd atoms in a PdO nanoparticle, bridged by an oxygen atom (Pd−O−Pd). Compared to other PdO nanoparticles and the reference PdO sample (red line in Figure ), however, the r ‐space spectrum of 0.04 wt % Pd/ZSM‐5 (blue line in Figure ) does not have such a distinct peak with the similar intensity as the Pd−Pd peak in PdO at ∼3.1 Å. Therefore, there is no evidence that any species or structure in 0.04 wt % Pd/ZSM‐5 contains Pd−O−Pd species, which indicates the absence of PdO nanoclusters.…”
Section: Figuresupporting
confidence: 54%
“…Therefore, it was determined that Pt was present in cation‐exchange sites. After oxidation, the CN for the R‐space EXAFS peak at around 2.0 Å (corresponding to the PtO shell) increased from 2 to 2.8, suggesting that Pt oxo species was formed [ 61 ] with a 1:1 Pt:O ratio that facilitates the CO oxidation reaction. This transformation progress was further supported by scanning transmission electron microscopy (STEM) results ( Figure A–G).…”
Section: Xas Analysis Of Sacs Supported By Crystalline Porous Materialsmentioning
confidence: 99%
“…11(b) This study revealed (Fig. 8) that replacing the bulky tetramethylethylenediamine (tmen) blocker with far less sterically demanding ethylenediamine (en), 55 results in the exclusive formation of triply interlocked trigonal prisms [(P17) 2 ]. However, on introducing guest molecules like trimesic acid (G3), the product that exclusively formed was the single prism with two guest molecules stacked inside the molecular architecture through π-π interactions.…”
Section: Neutral and Anionic Donorsmentioning
confidence: 99%